Combined Latissimus Dorsi/Teres Major Transfer and Superior Capsular Reconstruction Using Autogenous Biceps Tendon Effectively Relieves Pain and Improves Shoulder Function for Posterosuperior Irreparable Rotator Cuff Tears - Luis Alfredo Miranda, M.D.; Bo Taek Kim, M.D.; Paulo J. Llinás, M.D.; Chang Hee Baek, M.D.; Jean-David Werthel, M.D.; Jean Kany, M.D. (Arthroscopy, Sports Medicine, and Rehabilitation)
Purpose: To evaluate the clinical outcomes of fully arthroscopic latissimus dorsi (LD) and teres major (TM) transfer combined with superior capsular reconstruction (SCR) using long head of biceps (LHB) tendon in patients with posterior-superior irreparable cuff tears (PSIRCTs). Methods: A retrospective analysis was conducted on patients who underwent fully arthroscopic LDTM transfer with SCR using LHB tendon for PSIRCT between January 2021 and November 2023. The inclusion criteria were failure of conservative treatments, PSIRCTs with intact LHB, no or minimal glenohumeral arthritis, and minimum of one year follow-up. Patients were excluded if loss to follow-up, or follow-up of less than 1 year. Clinical assessments included the visual analog scale for pain, Simple Shoulder Test, Subjective Shoulder Value, and American Shoulder and Elbow Surgeons scores, and range of motion (ROM). Using 0.5 standard deviation distribution-based method, the percentage of the minimal clinically important difference was evaluated. Results: A total of 17 patients were included (10 male and 7 female), with a mean follow-up period of 16.3 ± 5.9 months (range, 12-27 moths). Significant improvements were observed across all outcome measures, including the visual analog scale (6.3 ± 2.0 to 2.0 ± 2.2), Simple Shoulder Test (3.3 ± 2.6 to 7.6 ± 2.9), Subjective Shoulder Value (34.1 ± 16.7 to 71.7 ± 13.8), Activities of Daily Living requiring active External Rotation (18.3 ± 8.3 to 26.2 ± 5.2), and American Shoulder and Elbow Surgeons (37.7 ± 21.8 to 77.3 ± 16.8) scores (all P < .001). The percentage of the minimal clinically important difference achieved for each score was 94.1%, 82.3%, 100%, 76.5%, and 82.3%, Shoulder ROM improvements were as follows: forward elevation increased from 123° ± 28° to 155° ± 30°, abduction improved from 87° ± 31° to 142° ± 31°, and external rotation increased from 21° ± 20° to 40° ± 10°. At the final follow-up, no patients experienced retears of transferred tendon, infection, progression of arthritis, or axillary nerve palsy. Conclusions: Fully arthroscopic LDTM with SCR using LHB tendon effectively alleviated pain and improved shoulder function in patients with PSIRCTs at short term follow-up. Significant improvements were observed in pain, patient-reported outcome measures, and ROM, with no progression of glenohumeral arthritis and no significant complications reported. Level of Evidence: Level IV, therapeutic case series.